Economic Threshold Density of Multi Species Weed for Direct Seeded Rice - Mamun , Md. Abdullah Al; Shultana, Rakiba; Rana, Md. Masud; Mridha, Abdul Jalil (Asian Journal of Agriculture and Rural Development, 2013)
We conducted two experiments in 2009 and 2010 at central part of Bangladesh to examine the effects of multispecies weeds on grain yield and to determine the economic threshold (ET) of weeds in direct seeded rice (DSR). The treatments consisted of 0, 5, 10, 20, 40, 80, 160 weeds m-2 and control (unweeded). Scirpus maritimus L. and Cyperus difformis L. were the most dominant weed species in year 1 and 2, respectively. Grain yield losses due to weed interference increased with weed population density increase. Panicle m-2, grains panicle-1, 1000-garin weight and grain yield varied significantly due to different weed density in both years of the study. Estimated ET were 5 and 7 weeds m-2 in year 1 and 2, respectively, assuming a weed free rice grain yield 5 ton ha-1, a crop price 210 ton-1, and weed control cost 30 ha-1.